Playing in the dark with online games for girls. (June 2017) - Sinker, Rebecca; Phillips, Mike; Rijke, Victoria de
Pregnant Rapunzel Emergency is part of a series of online free games aimed at young girls (forhergames.com orbabygirlgames.com ), where dozens of characters from fairy tales, children's toys and media feature in recovery settings, such as 'Barbie flu'. The range of games available to choose from includes not only dressing, varnishing nails or tidying messy rooms, but also rather more troubling options such as extreme makeovers, losing weight, or a plethora of baby showers, cravings, hospital pregnancy checks, births (including caesarean), postnatal ironing, washing and baby care. Taking the online game Pregnant Rapunzel Emergency as an exemplar of a current digital trend, the authors explore the workings of 'dark digital play' from a number of perspectives – one by each named author. The game selected has (what may appear to adults) several disturbing features in that the player is invited to treat wounds of the kind of harm that might usually be associated with domestic violence towards women.